The particular mapping of the nearest surroundings graph of the actual web page - Machova, Kristina (Array, 2009)
Summary: The paper presents an approach to partial mapping of a web sub-graph. This sub-graph contains the nearest surroundings of the actual web page. Our work deals with acquiring relevant Hyperlinks of a base web site, generation of adjacency matrix, the nearest distance matrix and matrix of converted distances of Hyperlinks, detection of compactness of web representation, and visualization of its graphical representation. The paper introduces an LWP algorithm – a technique for Hyperlink filtration. This work attempts to help users with the orientation within the web graph.